Argumentation and Disciplinary Training for University Geography Students - Díaz, Juan Pablo (2019)
The goal of this scientific article is to describe the different types of arguments made by advanced Geography students and understand how explicit and underlying epistemological assumptions of the study plan guide students in constructing these arguments. The methodological design is descriptive with a qualitative scope. The sample included 26 students from the state university of Resistencia, Argentina. Data collection sources included the Geography Major Study Plan and the result of arguments prepared by the students. It can be concluded that the current study plan is well directed at developing proper arguments in this subject matter. It is advised, however, that such curricular requirements do, in fact, undermine other geographic perspectives that are necessary skills for future geographers.